2018
DOI: 10.1002/anie.201713059
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐allyloxylated Cucurbit[7]uril Acts as an Unconventional Amphiphile To Form Light‐Responsive Vesicles

Abstract: Serendipitously, mono-allyloxylated cucurbit[7]uril (AO CB[7]) was discovered to act as an unconventional amphiphile which self-assembles into light-responsive vesicles (AO CB[7]VC) in water. Although the mono-allyloxy group, directly tethered on the periphery of CB[7], is much shorter (C4) than the hydrophobic tails of conventional amphiphiles, it played an important role in vesicle formation. Light-activated transformation of the allyloxy group by conjugation with glutathione was exploited as a remote tool t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…The unique recognition properties and biocompatibility enables their implementation as excipients (Lim et al, 2002; Kuok et al, 2017). Recent achievements in the preparation of CB derivatives and analogs allow their incorporation into more intricate and applied research lines (Ayhan et al, 2015; Kim et al, 2018; Koc et al, 2018; Park et al, 2018; Sun et al, 2018; Zhang et al, 2018a, 2019a) in an effort to by-pass intrinsic limitations of the parent CBs, such as their stringent selectivity for guest binding and the low intrinsic solubility of CB6 and CB8. We contend that this account will provide a platform for understanding the potential of CBs toward applications in pharmaceutically and medicinally research and assist us in designing and creating new CB-based assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…The unique recognition properties and biocompatibility enables their implementation as excipients (Lim et al, 2002; Kuok et al, 2017). Recent achievements in the preparation of CB derivatives and analogs allow their incorporation into more intricate and applied research lines (Ayhan et al, 2015; Kim et al, 2018; Koc et al, 2018; Park et al, 2018; Sun et al, 2018; Zhang et al, 2018a, 2019a) in an effort to by-pass intrinsic limitations of the parent CBs, such as their stringent selectivity for guest binding and the low intrinsic solubility of CB6 and CB8. We contend that this account will provide a platform for understanding the potential of CBs toward applications in pharmaceutically and medicinally research and assist us in designing and creating new CB-based assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, such CB‐derived systems often show large changes in constitution upon electrochemical stimulation, addition of competitive binders, changes in the ion intensity of the solution or changes in the pH of the medium, due to the changes in the binding affinities in CB–guest 9 . Therefore, many studies have focused on systems based on responsiveness in the host–guest chemistry of CBs 9–16 . The applications of stimuli‐responsive CBs can be further expanded by anchoring them onto polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular amphiphiles 1,2 have attracted growing interest due to the fascinating characteristics of dynamic and reversible nature of noncovalent interactions that endow them with a wide range of potential applications in many research areas including smart drug delivery [3][4][5][6] and advanced functional nanomaterials. [7][8][9][10] Representative amphiphiles with good responsiveness to various stimuli, such as pH changes, [11][12][13] enzymes, 14,15 and light irradiation, 16,17 have been designed and utilized to control drug action and enhance drug internalization efficiency in a tumour region based on the inherent attributes of the target sites in the intracellular microenvironment. Among them, glutathione (GSH)-responsive systems are of special interest, since it has been reported that certain tumorous intracellular compartments are characterized by reductive GSH at concentrations of ca.…”
Section: Introductionmentioning
confidence: 99%